Leaf herbivory by clover root weevil adults how much do they eat - Gerard, P.J.; Hackell, D.L. (New Zealand Plant Protection, 2005)
Populations of adult clover root weevil (Sitona lepidus) can inflict significant numbers of their distinctive feeding notches on the leaves of white clover (Trifolium repens) plants However it is assumed that because white clover is bred for defoliation the damage on established plants has little impact Two experiments were undertaken to quantify the daily leaf consumption levels of adult weevils and how this varied with weevil size and sex clover cultivar and previous leaf damage Overall adults consumed between 075 and 12 mg dry matter/day depending on cultivar and sex Sexual differences were observed between two contrasting clover cultivars with females consuming more Grassland Prestige and males Grasslands Kopu Clover dry matter loss through adult feeding was estimated at about 50 kg/ha from early summer until midwinter in the Waikato the period of peak adult activity